Differential skin immune responses in mice intradermally infected with Candida auris and Candida albicans - Abhishek Datta; Diprasom Das; Jeniel E. Nett; Jatin M. Vyas; Michail S. Lionakis; Shankar Thangamani (Microbiology Spectrum, 2023)
ABSTRACT Candida auris, an emerging multi-drug-resistant fungal pathogen, uniquely colonizes the human skin long term, leading to subsequent development of life-threatening invasive infections in humans. The factors regulating skin colonization of C. auris are not well understood. In this study, we established an intradermal mouse model of C. auris infection to define the innate and adaptive immune response to this emerging pathogen and compare it to Candida albicans. Our results indicate that compared to C. albicans-infected mice, C. auris-infected mouse skin tissue had significantly higher fungal load after 3 and 14 days post-infection. C. auris infection was associated with a significantly decreased accumulation of CD11b+ Ly6G+ neutrophils and increased numbers of CD11b+ Ly6 Chi inflammatory monocytes and CD11b+ CD207+ Langerhans cells at the site of infection. Furthermore, a significant decrease in the absolute numbers of type 3 innate lymphoid cells and Th17 cells was observed in C. auris-infected skin tissue. Taken together, our findings indicate that the skin immune responses are different between C. auris- and C. albicans-infected mice. The increased fungal load observed in C. auris-infected mouse skin tissue is associated with less potent innate and adaptive immune responses induced by this emerging pathogen relative to C. albicans. IMPORTANCE Candida auris is a globally emerging fungal pathogen that transmits among individuals in hospitals and nursing home residents. Unlike other Candida species, C. auris predominantly colonizes and persists in skin tissue, resulting in outbreaks of nosocomial infections. Understanding the factors that regulate C. auris skin colonization is critical to develop novel preventive and therapeutic approaches against this emerging pathogen. We established a model of intradermal C. auris inoculation in mice and found that mice infected with C. auris elicit less potent innate and adaptive immune responses in the infected skin compared to C. albicans. These findings help explain the clinical observation of persistent C. auris colonization in skin tissue.